Extent to Which the African Men are Able to Meet Physiological, Safety, Belongingness, Esteem and Self Actualization Needs for Themselves and Family in Daadab Refugee Camp, Garrisa County, Kenya (Global Journal of Human-Social Science, 2014)
The intention of this paper was to investigate the extent to which the African men in Dadaab refugee camps are able to meet physiological, safety, belongingness, esteem and self actualization needs for their families. To achieve this, the study sought to find out if the men were able to provide food for their children and if they were able to satisfy their sexual needs. The study further wished to establish if the men moved with their family members to the camp and if they were able to carry out their responsibilities as was expected of them and if they felt respected and fulfilled. Maslow's (1970) hierarchy of needs theory was used to ground the study. A sample of 192 respondents aged between15 year to 55 years was selected for the study with the majority coming from Somalia while a few came from Ethiopia, Sudan, south Sudan, Congo and Uganda.
Keywords: dadaab refugee camp; physiological needs; safety needs; love and belongingness; esteem; self actualization; african man; refugees